A Novel Application of Natural Peat for Solid-Phase Extraction of Pyrimethanil, Flumetralin, and Kresoxim-Methyl in Water Using Gas Chromatography-Mass Spectrometry. (14th June 2012) - Santos, Alex S. M. S. J.; Aquino, Adriano; Romão, Luciane P. C.; Navickiene, Sandro
Abstract : Natural peat was tested for extraction of pyrimethanil, flumetralin, and krexosim-methyl from water, with analysis using gas chromatography-mass spectrometry (GC-MS) in selected ion monitoring mode (SIM). Experiments were carried out at one fortification level (0.1 μ g L −1 ) and resulted in recoveries in the range 41–96%, with RSD values between 6.8 and 12.6% for natural peat as sorbent. Detection and quantification limits ranged from 0.02 to 0.05 μ g L −1 and from 0.07 to 0.1 μ g L −1, respectively, for the different pesticides studied. The method developed was linear over the range tested (0.07–4.0 μ g L −1 ), with correlation coefficients ranging from 0.9919 to 0.9989. Comparison between peat and commercial sorbents (C18 -bonded silica, ENVI-Carb, Florisil, silica gel, ENVI-Carb/LC-NH2 ) showed better performance of peat sorbent for flumetralin and kresoxim-methyl.